PERAN PENDIDIKAN DALAM MEMBANGUN TOLERANSI DI LINGKUNGAN PENDIDIKAN - Imam Asrofi; Ines Riski Agustin; Septi Nur Cahyati; Lailatul Fathkiyah (Al Madjid : jurnal Pendidikan Islam, 2025)
Education plays a very strategic role in forming a harmonious society, especially in the context of cultural, religious, and social diversity. This study focuses on the role of education in building an attitude of tolerance in the formal education environment. Using a literature study approach, this study explores various theories and previous research results to understand the relationship between education and tolerance. The results of the analysis show that education not only functions as a means of transferring knowledge, but also as a medium for forming character and moral values. Inclusive religious education and a collaborative approach to learning have proven effective in instilling diversity values. However, this study also found various challenges, such as the lack of integration of tolerance values ​​in the curriculum, social stereotypes, and the influence of a less supportive family environment. To overcome these obstacles, a strategy is needed that involves teacher role models, active family participation, and curriculum updates that emphasize character education more. This study is expected to be a theoretical contribution in understanding the role of education as the main instrument for forming a tolerant and inclusive society.